2020
DOI: 10.1186/s12981-020-00273-4
|View full text |Cite
|
Sign up to set email alerts
|

Daily variations of gut microbial translocation markers in ART-treated HIV-infected people

Abstract: Background: Increased intestinal barrier permeability and subsequent gut microbial translocation are significant contributors to inflammatory non-AIDS comorbidities in people living with HIV (PLWH). Evidence in animal models have shown that markers of intestinal permeability and microbial translocation vary over the course of the day and are affected by food intake and circadian rhythms. However, daily variations of these markers are not characterized yet in PLWH. Herein, we assessed the variation of these mar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…As mentioned previously, the BDG assay is helpful in the early detection of invasive fugal disease [ 31 , 32 ], including TM [ 33 ]. However, the elevation of BDG also have been linked to gut damage with increased intestinal permeability in HIV patients [ 34 , 35 ]. Furthermore, we found BDG was negatively correlated with the time required for blood culture turnaround in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, the BDG assay is helpful in the early detection of invasive fugal disease [ 31 , 32 ], including TM [ 33 ]. However, the elevation of BDG also have been linked to gut damage with increased intestinal permeability in HIV patients [ 34 , 35 ]. Furthermore, we found BDG was negatively correlated with the time required for blood culture turnaround in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…While our study failed to find an association between LPS and disease progression in our cohort of PLWHIV, it must be acknowledged that LPS measurement might not entirely capture the extent of MT, given its fluctuation during the day and its association with food intake and the fact that repeated measures of the markers post cART initiation were not available. A deeper understanding of the role of MT as cause of inflammation and disease progression in the course of cART could be gained by the comprehensive assessment of additional and reliable markers of both MT and inflammation, including the fungal translocation marker Beta d glucan (BDG) that has proven to maintaining stable plasma levels over 24 h, with stronger association with pro-inflammatory markers [ 47 49 ]. Also, a most comprehensive assessment of the interaction between several markers of microbial translocation and inflammation including IL-6 and D-dimer levels is strongly advocated to most finely unravel the possible mechanistic links between inflammation, MT and disease progression upon virally-suppressive cART.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also demonstrated that BDG levels were stable throughout 24 hours in ART-treated PLWH, as opposed to LPS levels ( 44 ). Interestingly, LPS levels increased after lunch and dinner, and decreased during the night, while BDG levels were stable over 24 hours.…”
Section: Validating Bdg As a Marker Of Microbial Translocation In Plwhmentioning
confidence: 80%